Supplemental protease improves in vitro disappearance of dry matter and crude protein in feather meal and copra meal for pigs - Ha,Dong Uk (2020)
ABSTRACT The aim of the present study was to determine the effects of supplemental protease on in vitro disappearance of dry matter (DM) and crude protein (CP) in feed ingredients for pigs. The test ingredients were three sources of feather meal (FM 1, FM 2, and FM 3), meat and bone meal, soybean meal, corn dried distillers grains with solubles, copra meal (CM), palm kernel meal, wheat, and corn. In experiment 1, in vitro ileal disappearance (IVID) of DM and CP were determined to represent the digestion and absorption of the stomach and small intestine of pigs. In experiment 2, in vitro total tract disappearance (IVTTD) of DM was determined to represent the digestion and absorption of the stomach, small intestine, and large intestine of pigs. The control group had 99% of a test ingredient and 1% of wheat bran. Protease originating from Bacillus spp. was supplemented to the control diet at the expense of wheat bran to make a treatment group (100,000 U/kg of sample). Protease supplementation increased the IVID of DM in FM 1 (39.8 vs. 37.5%) and CM (45.0 vs. 42.2%). In the protease supplementation group, the IVID of CP also increased in FM 1 (48.0 vs. 43.8%) and CM (85.3 vs. 77.5%). The supplemental protease increased the IVTTD of DM in FM 1 (43.9 vs. 42.1%), FM 3 (55.6 vs. 52.7%), and meat and bone meal (85.9 vs. 84.3%). Therefore, nutrient utilization of FM and CM can be improved by supplemental protease originating from Bacillus spp. based on in vitro assays.